3x-2y-2=0

Simple and best practice solution for 3x-2y-2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-2y-2=0 equation:


Simplifying
3x + -2y + -2 = 0
Reorder the terms:
-2 + 3x + -2y = 0
Solving
-2 + 3x + -2y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '2' to each side of the equation.
-2 + 3x + 2 + -2y = 0 + 2
Reorder the terms:
-2 + 2 + 3x + -2y = 0 + 2
Combine like terms: -2 + 2 = 0
0 + 3x + -2y = 0 + 2
3x + -2y = 0 + 2
Combine like terms: 0 + 2 = 2
3x + -2y = 2
Add '2y' to each side of the equation.
3x + -2y + 2y = 2 + 2y
Combine like terms: -2y + 2y = 0
3x + 0 = 2 + 2y
3x = 2 + 2y
Divide each side by '3'.
x = 0.6666666667 + 0.6666666667y
Simplifying
x = 0.6666666667 + 0.6666666667y

You can always share this solution

See similar equations:

| 3x*8x*14x= | | -5b+33=-5(b-6) | | 3d^2+25d+45=0 | | 21x^2-315=42x | | 7.25f-24.5=26.25 | | 6x+2y+3=0 | | 2(1+6k)=2+8(5+3) | | 3=6x+9 | | -8+5r=-3r+4r | | 16x+48=180 | | 10.1-5h+2.5=32.6 | | 9(-2)+2=6(-2)+4 | | 0.4t=0.72 | | 5.1x-2.6=11.68 | | f(-2)=3-(-2)-9 | | n-472=276 | | 7x+9=10y-4 | | 6a(3a-2)+5a=57 | | 38-2x=9 | | 12.15=1.9x+3.6 | | 11.70=2.10+0.8x | | -9+3+2x-9y-8= | | -48+-136= | | -3-2x=12+x | | 62-n=14 | | 8y-4x=104 | | 5x+6=2(3x+3) | | 9x-29=5x+15 | | m*10+m*13=138 | | 3.7x-28=30.46 | | -18+m/6=-10 | | 12-7y=-4.8 | | -4d+(-4d+5)5=-23 | | 2(n-3)=1-2n-7 | | k/8=13 | | -2a-2+9=3a-9 | | 2(3x-3)=3(5+3x) | | 9x^2+18x+7=0 | | 15x+26=146 | | 5+3x=12+2x | | 6x-5(2x+7)=4x-35 | | 2b-3=2b-3+4 | | 4x-2=2x-2 | | 2b-3=2b-3 | | -12x=-62 | | 3x-7(-x+4)=-2(x-5)+6x | | 12.5d+15=3.75 | | 9w-2w+8=4w-38 | | 3x+6=(5x) | | 7y+8=7x+9 | | k-(-178)=-231 | | 6z-3=z+4 | | 3x+7x-28=-2x+1+6x | | 6(m-7)+8=3m+15 | | Y=9x^2-12x+7 | | X-9y=-96 | | 3x+6=(5)x | | 10x-28=4x+10 | | 7p+11=46.7 | | X=2x-2+6 | | -10=w-38 | | 9(2m-1)=9m+72 | | =(-2/3)x-4 | | -5(m+6)=-3(4m-2) | | m*10-m*2=8 |


Related pages


49 prime factorizationwhat are the prime factorization of 39how to solve y 2x 1what is the prime factorization of 245multiples of 306cosx cos-x1234567890 098765432112.25 in fractionderivative of 5lnx2001 roman numerals63-19derivative of cos squared x3.14 x 12graph 2x y 2560-560sin 7xfactor x3 y35x 6y 7whats lcmderivative calculator lnhow to solve y 2x 5x 2-1 factoredwrite the decimal as a percent calculatorln kxalogpderive ln 2xgraph of sin3xcos pi 1factor 3x 2-7x-62sibsquare root of 53296x squaredfog solver2x 3 7xderivative of 1 cos2xsimplify 2x 3xbodmas solvergreatest common factor of 65prime factor of 2259x 7i 3 3x 7u25kg in lbsolve 5x 25derivative of 8xx 2-9 factored0.625 as a percent3x2 x 1800-2601.3125 as a fraction80000 pounds to dollarsprime factorization of 6003ln x-2logalogsquare root of 12.5prime factorization of 111what is the prime factorization of 1606.02x10 23maths 2cd155-10factor 3x 2 2x 5convert 49.99 to poundssquare root of 7056factor 5x-15what is the prime factorization of 400what is the prime factorization of 83fraction of 0.875sqrt 169solve x 2 2x-4 0prime factors of 1225graph 2-cosxctg 2xfactor 3x 2-5x-2prime factorization 105what is the lcm ofmultiples of 323prime factorize calculatorconvert percent to fraction calculatorfactorization of 63graph y 2cosxgraph x 2y 063-19log10 x 2